2020
DOI: 10.21203/rs.3.rs-22321/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of workplace violence against nurses in Iran and its related factors

Abstract: Background: Workplace violence is a relatively common problem in most jobs. The medical personnel especially nursing staff has been exposed to a great deal of violence from patients, companions, and colleagues, and it is necessary to determine its frequency by controlling it. The aim of this study was to investigate the prevalence of workplace violence against nurses. Materials and Methods: This study was a descriptive study which was performed among 200 qualified nursing staff working in Imam Hossain Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Regarding the gender pattern of the attacker in verbal violence, study data showed that men were more likely to engage in verbal violence than women. In the study of Aghilienjad et al, most verbal violence was committed by patients and their companions [13]. In the study of Gerbrich et al, The most frequent perpetrators of non-physical violence were patients and their companions [25].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding the gender pattern of the attacker in verbal violence, study data showed that men were more likely to engage in verbal violence than women. In the study of Aghilienjad et al, most verbal violence was committed by patients and their companions [13]. In the study of Gerbrich et al, The most frequent perpetrators of non-physical violence were patients and their companions [25].…”
Section: Discussionmentioning
confidence: 98%
“…However, due to the particular nature of emergency care, this communication might change to some degree of violence [12]. Many studies have been conducted about workplace violence in Guilan Province, Iran [13][14][15]. However, there is a lack of information about the underlying factors from the perspective of pre-hospital EMS personnel [15][16][17].…”
Section: Introductionmentioning
confidence: 99%